Acetaminophen/paracetamol: A history of errors, failures and false decisions - Brune, Kay; Renner, Bertold; Tiegs, G. (European Journal of Pain, 2015)
Acetaminophen/paracetamol is the most widely used drug of the world. At the same time, it is probably one of the most dangerous compounds in medical use, causing hundreds of deaths in all industrialized countries due to acute liver failure (ALF). Publications of the last 130 years found in the usual databases were analyzed. Personal contacts existed to renowned researchers having contributed to the medical use of paracetamol and its precursors as H.U. Zollinger, S. Moeschlin, U. Dubach, J. Axelrod and others. Further information is found in earlier reviews by Eichengrün, Rodnan and Benedek, Sneader, Brune; comp. references. The history of the discovery of paracetamol starts with an error (active against worms), continues with a false assumption (paracetamol is safer than phenacetin), describes the first side-effect 'epidemy' (phenacetin nephropathy, drug-induced interstitial nephritis) and ends with the discovery of second-generation problems due to the unavoidable production of a highly toxic metabolite of paracetamol N-acetyl-p-benzoquinone imine (NAPQI) that may cause not only ALF and kidney damage but also impaired development of the fetus and the newborn child. It appears timely to reassess the risk/benefit ratio of this compound.
EVALuna2:8514